Radiosynthesis of Stable 198Au-Nanoparticles by Neutron Activation of αvβ3-Specific AuNPs for Therapy of Tumor Angiogenesis - Güllü Davarci; Carmen Wängler; Klaus Eberhardt; Christopher Geppert; Ralf Schirrmacher; Robert Freudenberg; Marc Pretze; Björn Wängler (MDPI AG, 2023)
This paper reports on the development of stable tumor-specific gold nanoparticles (AuNPs) activated by neutron irradiation as a therapeutic option for the treatment of cancer with high tumor angiogenesis. The AuNPs were designed with different mono- or dithiol-ligands and decorated with different amounts of Arg-Gly-Asp (RGD) peptides as a tumor-targeting vector for αvβ3 integrin, which is overexpressed in tissues with high tumor angiogenesis. The AuNPs were evaluated for avidity in vitro and showed favorable properties with respect to tumor cell accumulation. Furthermore, the therapeutic properties of the [198Au]AuNPs were evaluated in vitro on U87MG cells in terms of cell survival, suggesting that these [198Au]AuNPs are a useful basis for future therapeutic concepts.